Learning to Teach as a Spectator or a Participant-Ideas of Vocational Learning in Policy on Teacher Education - Sandra Jederud (MDPI AG, 2022)
This article explores how ideas about teacher student learning are expressed in policy documents, especially the school-based part of teacher education in the Swedish educational system. The study concerns how these parts of the education process are outlined through two reforms, one in 2001 and one in 2011. Of particular interest in the article is how these reforms represent, and to some extent, produce ideas for learning the teaching profession in relation to the specific context of practicum, and that this context pertains to specific knowledge, theoretical and practical knowledge. However, the analysis of the documents points towards a tension between theory and practice. By additionally analyzing policy documents on a local level, where the national policy is operationalized, the tension between theory and practice becomes more explicit. By introducing the notion of spectatorship knowledge and participatory knowledge, two different visions of students' learning emerge in policy. However, the relation between these two perspectives is problematic, as will be shown in the concluding part of the article. In conclusion, it is suggested that rather than muddling spectatorship knowledge and participatory knowledge together, teacher education programmes should provide for conditions where these knowledge forms are better taken care of.